Multiple online-HPLC methodologies and biological properties of leaves and stem barks extracts of Chrysanthellum indicum - Nilofar; Sinan, Kouadio Ibrahime; Eyüpoğlu, Ozan Emre; Ferrante, Claudio; Ahmed, Shakeel; Etienne, Ouattara Katinan; Zengin, Gökhan (Elsevier Inc., 2024)
Chrysanthellum indicum, an annual herb with yellow flowers, is used as a functional food in Asia and Africa for health purposes. In this study, we thoroughly investigated the characterization of phytochemicals within C. indicum's ethyl acetate, water, and methanolic extracts from both its bark and leaves. This was achieved through the utilization of the Folin Ciocalteu and aluminum trichloride assays. Moreover, the antioxidant properties of these extracts were comprehensively assessed employing microplate-based assays including ABTS, DPPH, CUPRAC, FRAP, MCA, and PBD, alongside online HPLC-based assays namely ABTS, DPPH, CUPRAC, and FRAP. Furthermore, the inhibitory activity against a range of enzymes, including AChE, BChE, tyrosinase, ?-amylase, and ?-glucosidase, was ascertained. The tested ethyl acetate extracts from bark and leaves had higher content of total phenolic and flavonoid compared to methanol and water extracts. Additionally, the bark extract exhibited superior antioxidant properties in the in vitro antioxidant assays. Meanwhile, in the realm of online HPLC antioxidant analysis, an effective method has been discovered for swiftly determining the individual antioxidant capacity of compounds within both standard solutions and extract. Within the entirety of the samples subjected to scrutiny, rutin surfaced as the foremost antioxidant, exhibiting its prominence at wavelengths of 280 nm, 595 nm, and 450 nm. Following suit, quercetin emerged as the second most abundant antioxidant, noticeable at wavelengths of 517 nm and 734 nm, both in leaves and bark extracts. Significantly, the extracts derived from both bark and leaves demonstrated noteworthy effectiveness in inhibiting the tyrosinase enzyme. Thus, our study indicates that Chrysanthellum indicum could serve as a promising reservoir of natural bioactive compounds, making it suitable for the formulation of health-promoting applications.
Keywords: Antioxidant; Chrysanthellum; Enzyme Inhibition; Flavonoid; Online HPLC